Systemic sclerosis is a risk factor of incident psoriasis: results from a nationwide cohort study - Kwon, Oh Chan; Han, Kyungdo; Park, Min-Chan (Frontiers in Immunology, 2023)
Objective Although the co-existence of systemic sclerosis (SSc) and psoriasis (PsO) has been reported, the risk relationship between the two diseases remains unclear. We aimed to assess whether SSc is associated with the risk of incident PsO. Methods From the Korean National Health Insurance Service database, 4,933 patients with SSc and 24,665 age- and sex-matched controls were selected. Hazard ratios (HRs) and 95% confidence intervals (CIs) for incident PsO were estimated using multivariable Cox proportional hazard models adjusted for known risk factors of PsO. Further, we selected individuals whose health check-up data were available (2,355 patients with SSc and 11,775 age- and sex-matched controls). In this population, we further adjusted for additional risk factors of PsO using the health check-up data. Results In the analysis of 4,933 patients with SSc and 24,665 age- and sex-matched controls, incidence rates of PsO in patients with SSc and controls were 10.26 and 3.20 per 1,000 person-years, respectively. After adjusting for risk factors of PsO, patients with SSc had a significantly higher risk of incident PsO (adjusted HR: 3.055 [95% CI: 2.597, 3.594]). Moreover, in the analysis of individuals who had health check-up data, additional risk factors of PsO were further adjusted; the result also showed that patients with SSc have a significantly higher risk of incident PsO (adjusted HR: 2.820 [95% CI: 2.207, 3.603]). Conclusion Patients with SSc had a 3-fold higher risk of developing incident PsO than controls, independent of known risk factors of PsO.